Teacher's Perception of Training Middle Managers in Leadership and Management Skills: A Survey at Al-Hidayah Foundation - Hamid, Syifa Fadhilah (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2022)
Training middle managers comes up as an essential part to be done in a school area since middle managers play a critical role in school development and effectiveness as well as crucial to the success of the school. However, numerous recent researches indicate that middle managers are not receiving the relevant support and training they require to fulfil their roles. While other researchers argued that there has been some improvement, there continues to be a lack of adequate and effective training for middle managers prior to them taking up their roles, including those aspiring to their positions. Furthermore, it identified the fact that positions in middle management are increasing in number as well as complexity, yet middle managers are being appointed to the positions without the relevant support or training. Thus, the teacher’s perceptions are needed to highlight more about the importance of training middle managers in leadership and management skills. This study is a survey study which is aimed to get an empirical data about teachers' perceptions of training middle managers in leadership and management skills at Al-Hidayah foundation. The writer used modified questionnaire to gather the data. All the participants are considered as middle managers at Al-Hidayah Foundation including principal, vice principle and other Heads of Department. The result shows that training middle managers in leadership and management skills can give them positive impact to build their professionalism as teacher and manager